The Collaborative Institute for Education Research, Evidence and Impact: a Case Study in Developing Regional Research Capacity in Wales. (1st March 2019) - Tyler, Emily; Watkins, Richard; Roberts, Sarah; Hoerger, Marguerite; Hastings, Richard; Hulson- Jones, Amy; Hughes, Carl
In this case study, we describe the work undertaken since 2004 in the journey to develop a collaborative model of working aimed at building the capacity and relevance of education research and evaluation across the North Wales region. The work has culminated in 2017 with the creation of a collaborative research institute, the Collaborative Institute for Education Research, Evidence and Impact (CIEREI). CIEREI is a formal strategic collaboration between GwE (the Regional School Effectiveness and Improvement Service for North Wales), Bangor University, schools, and other bodies and institutions interested in education outcomes. The primary aim of CIEREI is to support improving outcomes for children through schools, and to contribute to teacher education and building regional capacity in school- led, co- constructed close- to- practice impact research. CIEREI's establishment is the third phase in the development of a regional research and evaluation collaboration across North Wales.